Students’ Views On The Lecturers’ Delivery Of Lesson - Md Yusof, Masdinah Alauyah; Shahrom, Khairunnisaq (2010)
The ability of the lecturer to deliver a good and clear lesson is essential as it would help the process of understanding the lecture. By right, a lecturer should have practice good lesson delivery behaviours in his/her classroom. Hence, the study is to evaluate the Universiti Teknologi Malaysia (UTM) TESL students’ views on the level of the lecturers’ ability to exhibit clear and comprehensible lesson delivery using the specific elements of teaching behaviours. Apart from that, this study also seeks to examine the possible effects of clear lesson delivery on TESL students. It is also to obtain suggestions on how the lecturers could improve in lesson delivery in the future. The research instrument used is the questionnaire to collect the data from Year 1, 2, 3 and 4 TESL classes. The findings are then discussed according to the research questions. It was found that (1) TESL students were mostly agreed that their lecturers’ lesson delivery is clear by practicing specific elements of clear teaching behaviours which are answering students’ questions wisely, giving clear and precise explanation, providing additional information and describing the work to be done by the students, (2) lecturers’ clear lesson delivery give vital impacts on TESL students which are getting important main points, reducing frustration and increasing satisfaction and lastly (3) the suggestions by TESL students for improved lesson delivery by assisting students individual help, organizing materials in a systematic way and providing illustrations. It is hoped that the research findings could help the future research and benefit the readers, the lecturers and the newcomers to the teaching field.